Proximate and Some Micronutrients (Zn, Se, Fe and I) Assessed in Goat Milk, and Cattle Milk in Sokoto, Nigeria - Salah, Nura Maiakwai; Daji, Atiku Yari Dogon; Umar, Rilwanu; Umar, AI; Sarkingobir, Yusuf (Jurnal Medis Islam Internasional, 2023)
Background: Malnutrition, poverty, and information scarcity are some of the major issues affecting people in West African region. Thus, it is imperative to divulge nutritional information from a cheap and accessible food (the milk) in the region. Objective: This study aimed at performing a proximate and Zn, Se, Fe and I micronutrients determination in goat and cattle milk in Sokoto, Nigeria. Method: The concentrations of zinc, selenium, iron, iodine present in goat and cattle in Sokoto, Nigeria were determined using standard methods and materials of analytical grade.  Results: The result reveals (< 0.05) Zn, Se, Fe, and I in goat as follows: 9.10 ± 0.05 ppm, 2.32 ± 0.004 ppm, 10.5 ± 0.05 ppm and 7.8 ± 0.01 ppm. In cattle, the concentrations for Zn, Se, and Fe are: 5.12 ± 1.05 ppm, 1.13 ± 0.005 ppm, 9.5 ± 0.02 ppm, and 5.9 ± 0.02 ppm. The proximate values of moisture content, ash content, protein, and fat in milk collected from goat are as follows respectively: 90.21%, 0.56 %, 3.23%, and 2.44%. The proximate values in cattle milk are: 70.11%, 0.50%, 2.11%, 2.11% and 2.21% for water content, ash content, protein content, and fat content respectively. Conclusions: Thus, the goat milk contains higher proximate contents (such as fat, water, carbohydrate, and ash), Zn, Fe, and Se than the cow milk. It is imperative for the public to properly utilize milk for its nutritious benefits.